The Indigenous Muslim Minority Group In Ma’undai (Keo) of Central Flores: Between the House of Islam and the House of Culture - Philipus Tule (Antropologi Indonesia, 1998)
"...[...] However, the previous studies, except for those recent studies by Fox (1984), Gomang (1993), and Barnes (1995/1996), have no great anthropological value. This paper will illustrate the struggle of the indigenous Muslims in Keo of Central Flores (NTT) to answer the quest of how to maintain their multiple self-identities both as Muslims and as indigenous people who are committed to a particular local culture. Their notion of Dar al-Islam (House of Islam) as a part of their Muslim way of life and their appreciation of the local culture expressed through the notion of a house (House of Culture), as represented by Muslim community of Ma'undai in Keo, will be the main focus of my study, with particular reference to the concept of 'house-based society' as expressed through their cult-houses or ritual houses and social organization."